D'Après Blanche Neige - Decointet, Hugues (France, 2010)
A documentary essay, both fiction - an adaptation of the text "Snow White" by Robert Walser and narrative about another film, eponymous, the Portuguese filmmaker Joao César Monteiro: a film without image, all in black from which only emerge the voices of the Walser dialogue. It is not a question of showing what Monteiro had radically hidden, but of finding this gesture through its "traces": memories of the shooting of the comedian Hugues Quester or Monteiro himself, places of scenery like the Botanical Garden from Lisbon, scenes from Walser's play, conducive to twists and turns to other stories, such as the story of Grimm ...
Verzio Film Festival Submission
Keywords: Documentary films